The origins of the modern world a global and environmental narrative from the fifteenth to the twenty-first century - Marks, Robert 1949- (Rowman & Littlefield, 2015)
"Now in a new edition, this clearly written and engrossing book presents a global and environmental narrative of the origins of the modern world since 1400. Robert Marks constructs a story in which Asia, Africa, and the New World play major roles and points to the resurgence of Asia and the vastly changed relationship of humans to the environment"--Provided by publisher